Clinical reasoning for acute dyspnoea: comparison between final-year medical students from discipline- and competency-based undergraduate programmes - Anja Czeskleba (BMC Medical Education, 2020)
Abstract Clinical reasoning for acute dyspnoea: Comparison of final-year medical students from discipline- and competency-based undergraduate programmes. Background The global shift to competency-based medical education aims to improve the performance of its trainees, including in the key competency domain of clinical reasoning. However, research on whether such education actually improves clinical reasoning is sparse. The purpose of this study is to compare assessed clinical reasoning performance in digitally presented cases of acute dyspnoea between final-year medical students from a traditional, discipline-based and those from an integrated, competency-based undergraduate programme. Methods A total of 60 medical students in their final-year clerkships participated in the study; 30 were from a discipline-based programme, and 30 were from a competency-based programme of the same faculty. The students completed a knowledge test consisting of 22 single choice items and a computer-based test of clinical reasoning with six video-based case scenarios with different underlying diseases leading to dyspnoea. The operationalized measures of clinical reasoning were the number and relevance of the diagnostic tests chosen, time to diagnosis and diagnostic accuracy. Results The two groups did not differ in their knowledge of the acute dyspnoea content domain. With regard to clinical reasoning, the selection of relevant tests, time required to make a diagnosis and accuracy of the diagnosis varied across the six case scenarios in both groups. However, the results from the measures of the clinical reasoning process did not differ between the students from the two types of undergraduate medical programmes. No significant differences were found with regard to the selection of relevant diagnostic tests (M = 63.8% vs. M = 62.8%), the time to a diagnosis (M = 128.7 s vs. M = 136.4 s) or the accuracy of diagnosis (M = 82.2% vs. M = 77.0%). Conclusions Key indicators of the clinical reasoning process, when assessed with objectively measured parameters, did not differ between final-year medical students from a traditional, discipline-based and those from an integrated, competency-based undergraduate programme in the domain of acute dyspnoea. The results substantiate and expand those of previous studies based on subjective assessor ratings that showed limited change in the clinical reasoning performance of medical students with competency-based undergraduate education.